Covid -19: The Impact On Malaysian Visual Arts Scene - Mohd Fauzi Sedon; Che Zalina Zulkifli; Mohd Zahuri Khairani; Karthigayan Gunesegaran; Abdul Aziz Zalay (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This paper discusses the impact of COVID-19 on the Visual Arts industry in Malaysia. In general, this pandemic has affected various forms of artistic activities and the income of visual arts artists and galleries. The cancellation of art projects and exhibitions has greatly affected the artist's source of income as well as disrupted the sale of works and forms of art appreciation. The crisis has also opened up a new form to the visual arts industry by looking at alternative approaches to the continuity of the arts field by switching to virtual or online methods. This emerging crisis of COVID-19 might be the starting point for all art practitioners including artists, art critics, galleries/museums, collectors, and curators in using the online space to continue to capitalize on and expand the Visual Arts industry. Design/methodology/approach: Review approach. Findings: The COVID-19 pandemic has made a huge impact on the country's Visual Arts industry where a wide range of art activities cannot be implemented and opened up opportunities for online activities Practical implications: Exhibition and sale of works through online approach has become one of the main methods that support the Visual Arts industry with the application of a combination of the latest technologies such as VR and AI that enable the representation of real experiences in the context of art appreciation. Originality/value: This paper is original. Paper type: This paper can be categorized as a viewpoint